Population Growth and Forest Sustainability in Africa - Simplice A. Asongu; Brian Jingwa (African Governance and Development Institute (AGDI), 2011)
Recent distressing trends in climate change, population explosion and deforestation inspired this paper, which completes existing literature by providing empirical justification to hypothetical initiatives on the impact of population growth on forest sustainability in Africa. Using three instruments of forest exploitation, the study shows how rural, agricultural and national population growths affect forest-area and agricultural-land. In this particular study the findings indicate that instruments of forest exploitation do not explain changes in forest-area and agricultural-land beyond population growth mechanisms. Hence, population growth channels are a driving force by which forest-area and agricultural-land are depleted and expanded respectively. As a policy implication in the process of deforestation, a balanced approach is needed to take account of the interests of both; a green economy promoting sustainable development and the growing population needs.
Keywords: J10; L73; N50; O13; Q23; 330; Demography; Forestry; Agriculture; Environment; Africa